Cold- and hot-classified botanical drugs differentially modulate gut microbiota: linking TCM emic classification to microbial ecology - Huan Yang; Chenyi Shao; Zhihao Liu; Xiaoyu Zhang; Yinhui Liu; Jing Xiao; Li Tang (Frontiers in Pharmacology)
IntroductionTraditional Chinese Medicine (TCM) classifies botanical drugs based on their thermal properties (an emic classification system), categorizing them as “cold” (e.g., “clearing heat” for anti-inflammatory effects) or “hot” (e.g., “warming the middle” for metabolic enhancement). However, the specific roles of these botanical drugs in restoring gut microbiota dysbiosis remain unclear. This study aimed to explore whether TCM-classified cold and hot botanical drugs differentially restore gut microbiota dysbiosis and host physiology in antibiotic-treated mice.MethodsMice with antibiotic-induced dysbiosis were treated with eight TCM-classified botanical drugs (four cold: Rheum palmatum L., Scutellaria baicalensis Georgi, Senna alexandrina Mill., Coptis chinensis Franch.; four hot: Codonopsis pilosula (Franch.) Nannf., Astragalus membranaceus (Fisch.) Bunge, Angelica sinensis (Oliv.) Diels, Panax ginseng C.A.Mey.) for 20 days. Gut microbiota were analyzed via 16S rRNA sequencing on days 5, 10, 15, and 20, alongside physiological parameters including blood glucose, serum lipids, TNF-α, adiponectin, and intestinal histomorphology.ResultsBy day 20, all botanical drugs restored the diversity and ranking of dominant genera (those with >10% abundance, such as Lactobacillus and unclassified Muribaculaceae). However, cold-classified drugs, traditionally associated with anti-inflammatory effects, selectively enriched anti-inflammatory taxa, including Akkermansia and Bifidobacterium. In contrast, hot-classified drugs, linked to metabolic enhancement, promoted metabolic-modulating genera such as Clostridia and Eubacterium coprostanoligenes. These differential enrichments corresponded with the therapeutic principles defined by TCM: cold-classified drugs reduced serum TNF-α levels (P < 0.01), demonstrating anti-inflammatory effects, whereas hot-classified drugs improved lipid profiles (TG: P < 0.001), thereby promoting metabolic modulation.DiscussionTCM-classified cold and hot botanical drugs universally stabilize dominant microbiota while differentially modulating low-abundance taxa. The enrichment of Akkermansia (cold) and Clostridia (hot) offers a microbiota-driven validation of TCM’s empirical classification framework. These findings connect traditional knowledge with microbial ecology, underscoring the potential of TCM-guided microbiota modulation for precision therapies.